2010
DOI: 10.1375/twin.13.4.330
|View full text |Cite
|
Sign up to set email alerts
|

Are Attitudes Towards Economic Risk Heritable? Analyses Using the Australian Twin Study of Gambling

Abstract: This study employs multiple regression models based on DeFries and Fulker (1985), and a large sample of twins, to assess heritability in attitudes towards economic risk, and the extent to which this heritability differs between males and females. Consistent with Cesarini et al. (2009), it is found that attitudes towards risk are moderately heritable, with about 20 percent of the variation in these attitudes across individuals being linked to genetic differences. This value is less than one-half the estimates r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 25 publications
4
29
0
Order By: Relevance
“…A behavioral genetics approach is first taken, based on Le, Miller, Slutske and Martin (2010), to review findings on gender differences in attitudes towards economic risk. The risk variable is then related to earnings using estimating equations based on both human capital and behavioral genetics models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A behavioral genetics approach is first taken, based on Le, Miller, Slutske and Martin (2010), to review findings on gender differences in attitudes towards economic risk. The risk variable is then related to earnings using estimating equations based on both human capital and behavioral genetics models.…”
Section: Introductionmentioning
confidence: 99%
“… 3 See Le, Miller, Slutske and Martin (2010) for discussion of the statistical properties of these estimators, and of the power of the multiple regression model compared to maximum likelihood estimation of the genetic and common environmental parameters from the covariance structure of the data. …”
mentioning
confidence: 99%
“…() and Le et al. (, ). The data were collected over 2004–2007 from members of the Australian Twin Registry Younger Twin Cohort.…”
Section: Datamentioning
confidence: 98%
“…While the earlier research using these data by Le et al. (, ) applied a “years of full‐time education equivalent” to these education categories, in the research below we follow Kidd and Meng () and specify a separate dichotomous variable for each education category (with the group of early school leavers as the benchmark group).…”
Section: Datamentioning
confidence: 99%
“…Four recent studies provide substantiation of the heritability of risk. One of the largest twin studies exploring risk preferences was conducted with a total of 1,875 twin pairs in Australia, comprising 867 pairs of identical twins and 1,008 pairs of nonidentical twins (Le et al 2010). This study found that approximately 20 percent of the variation in risk is linked to genetic differences.…”
Section: Twin Studies Provide Estimates Of Heritability Of Risk Prefementioning
confidence: 99%